El uso del material didáctico concreto utilizado por los docentes y su incidencia en el desarrollo de destrezas con criterio de desempeño en el bloque curricular geométrico, en los estudiantes del nivel superior de octavo grado de educación general básica del colegio Dr. Baltazar Aguirre, de la parroquia Quinara, cantón y provincia de Loja”. Periodo 2012-2013. Lineamientos alternativos - Armijos Gaona, Fanny Maritza (2014)
In the teaching-learning process, the employment of concrete didactic resources, they require that the educational ones are qualified and maintain an attitude porosity in front of their students, this situation demands to the educational ones to be upgraded in strategic of teaching that influence in the context of the educational practice. In this mark the present investigation the one is developed which begins with the necessity of giving answer to the following problem: how they influence the use of the material didactic concrete used in the geometric curricular block for the development of dexterities with acting approach in the students of eighth year of Basic General Education of the school Dr. Baltazar Aguirre, of the parish Quinara, canton and county of Loja, year lectivo 2012-2013?. The objectives that guided the investigation are oriented to determine the level of knowledge that you/they have the educational ones and the incidence of the use of the concrete material in the development of dexterities with acting approach in the geometric curricular block in the students of the eighth year of Basic General Education of the school Dr. Baltazar Aguirre, of the parish Quinara, Canton and County of Loja, period 2012-2013. The results of the investigation are presented in squares and statistical graphics, among those of more transcendency they are considered the following ones: the educational one doesn't possess clear knowledge and it is not able to be able to develop the dexterities with approach of acting in a significant way in their students, it is observed that in the teaching of the geometric curricular block didactic resources are used that are considered traditional and they are managed exclusively for educational, the investigation determined that there is not concrete didactic material in the institution, the educational one knows the benefits that it produces the use of the concrete material and the results partly that they are obtained in the process teaching-learning, however, he/she has not received training on the use and elaboration of concrete didactic material, the level of development of the dexterities with acting approach reached by the investigated students is qualified of half to under, the use of didactic material sums up partly it has facilitated them the learning of the geometry, a high percentage of students was not able to solve the problems outlined in the test of knowledge correctly, this reflective its limitation of knowledge, when not being able to graph the problem to understand it, to determine the data in appropriate form, to reason him, to apply the most convenient procedure and to verify their results.